A large and enigmatic new eleutherodactyline frog (Anura, Strabomantidae) from Serra do Sincora Espinhaco range, Northeastern Brazil - Cassimiro, José; Verdade, Vanessa K.; Rodrigues, Miguel T. (Zootaxa, 2008)
We describe a new species of a large eleutherodactyline frog from the mountain rocky meadows (“campos rupestres”) of the Serra do Sincorá, Espinhaço mountain range, Mucugê municipality, State of Bahia, Brazil. The new species is promptly diagnosed from all the other Brazilian eleutherodactylines by its large size (males SVL 40.3–41.1; females SVL 75.2–79.7mm), broad head (head width 43–49% of SVL), presence of frontoparietal crests, pars fascialis of the maxilla deepened, discs absent on fingers, toes with poorly developed discs, first and second toes ridged, and tarsal fold absent. On the basis of these characters the new species is attributed to the genus Strabomantis up to now restricted to southern part of Central America and northwest part of South America.